Immunological Insights in Equine Recurrent Uveitis - Degroote, Roxane L.; Deeg, Cornelia A. (Frontiers in Immunology, 2021)
Horses worldwide suffer from equine recurrent uveitis (ERU), an organ-specific, immune-mediated disease with painful, remitting-relapsing inflammatory attacks alternating with periods of quiescence, which ultimately leads to blindness. In course of disease, both eyes can eventually be affected and since blind horses pose a threat to themselves and their surroundings, these animals have to be killed. Therefore, this disease is highly relevant for veterinary medicine. Additionally, ERU shows strong clinical and pathological resemblance to autoimmune uveitis in man. The exact cause for the onset of ERU is unclear to date. T cells are believed to be the main effector cells in this disease, as they overcome the blood retinal barrier to invade the eye, an organ physiologically devoid of peripheral immune cells. These cells cause severe intraocular inflammation, especially in their primary target, the retina. With every inflammatory episode, retinal degeneration increases until eyesight is completely lost. In ERU, T cells show an activated phenotype, with enhanced deformability and migration ability, which is reflected in the composition of their proteome and downstream interaction pathways even in quiescent stage of disease. Besides the dysregulation of adaptive immune cells, emerging evidence suggests that cells of the innate immune system may also directly contribute to ERU pathogenesis. As investigations in both the target organ and the periphery have rapidly evolved in recent years, giving new insights on pathogenesis-associated processes on cellular and molecular level, this review summarizes latest developments in ERU research.